PEMAHAMAN SANTRI TENTANG WAWASAN MODERASI BERAGAMA DI PONDOK PESANTREN DARUL ISTIQAMAH KABUPATEN SINJAI - Wahyuni; Rahman, Ratnah (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2024)
This article explains the students' understanding of the insight into religious moderation at the Darul Istiqamah Islamic Boarding School, Sinjai Regency. The approach used in this research is a case study. To collect data the author used several techniques in data collection, namely observation, interviews and documentation. The results of this research explain that the students' understanding of the insight into religious moderation in religion at the Darul Istiqamah Islamic Boarding School is more about efforts to implement fundamental religious values ​​related to attitudes and behavior amidst plurality and diversity in social life.